Cellular immunotherapy in breast cancer: The quest for consistent biomarkers. (November 2020) - Venetis, Konstantinos; Invernizzi, Marco; Sajjadi, Elham; Curigliano, Giuseppe; Fusco, Nicola
Highlights: Unresponsiveness and/or resistance to pharmacotherapy occur in many breast cancers. Cellular immunotherapy is an emerging treatment option. Cellular immunotherapy exploits patients' immune cells for therapeutic purposes. Several clinical studies involve adoptive cell therapy and dendritic cell vaccines. Patients' selection should ideally be biomarker based. Abstract: Breast cancer is the most common malignancy in women worldwide, with a relatively high proportion of patients experiencing resistance to standard treatments. Cellular immunotherapy (CI), which is based on the extraction, modification, and re-infusion of the patient's immune cells, is showing promising results in these patients. Among CI possible approaches, adoptive cell therapy (ACT) and dendritic cell (DC) vaccination are the most comprehensively explored in both primary/translational research studies and clinical trials. ACT may include the use of tumor-infiltrating lymphocytes (TILs), T cell receptor (TCR)-, or chimeric antigen receptor (CAR)-engineered T-cells. There are indications suggesting that a biomarker-based approach might be beneficial in effectively selecting breast cancer patients for CI. Here, we sought to provide the current knowledge of CI in breast cancer, focusing on candidate biomarkers, ongoing clinical trials, limitations, and immediate future perspectives.